Protein and Carbohydrate Exopolymer Particles in the Sea Surface Microlayer (SML) - Thornton, Daniel C. O.; Brooks, Sarah D.; Chen, Jie (Frontiers in Marine Science, 2016)
Exchanges of matter and energy between ocean and atmosphere occur through the sea surface microlayer (SML). The SML is the thin surface layer of the ocean at the ocean-atmosphere interface that has distinctive physical, chemical and biological properties compared with the underlying water. We measured the concentration of two types of exopolymer particles in the SML and underlying water in the Pacific Ocean off the coast of Oregon (United States) during July 2011. Transparent exopolymer particles (TEP) are defined by their acidic polysaccharide content, whereas Coomassie staining particles (CSP) are composed of protein. TEP and CSP were ubiquitous in the SML. TEP were not significantly enriched in the SML compared with the underlying water. CSP were significantly enriched in the SML, with an enrichment factor (EF) of 1.4 to 2.4. The distribution of exopolymer particles in the water and microscopic imaging indicated that TEP and CSP are distinct populations of particles rather than different chemical components of the same particles. Dissolved polysaccharides were not enriched in the SML, whereas monosaccharides had an EF of 1.2 to 1.8. Sampling occurred during the collapse of a diatom bloom, and diatoms were found both in the water column and SML. While there were living diatoms in the samples, most of the diatoms were dead and there were abundant empty frustules covered in layer of TEP. The collapsing diatom bloom was probably the source of exopolymer particles to both the SML and underlying water. Exopolymer particles are a component of the SML that may play a significant role in the marine carbon and nitrogen cycles, and the exchange of material between ocean and atmosphere.